2015
DOI: 10.1596/1813-9450-7484
|View full text |Cite
|
Sign up to set email alerts
|

Mobility, Scarring and Job Quality in Indonesia's Labor Market

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…New entrants to this sector upon crisis will suffer in the long run. It becomes difficult to move out of the informal sector for permanent higher-paying jobs in other sectors, due to issues like lack of training (Naidoo, Packard, & Auwalin, 2015). Even if workers move to the formal sector, they will only earn the lowest-paying wages, an option most workers would not prefer even if it comes with insurance benefits, highlighting why this sectoral shift becomes more rigid throughout the years.…”
Section: Shift In Job Sectors and Increased Mobility From Import-oriementioning
confidence: 99%
“…New entrants to this sector upon crisis will suffer in the long run. It becomes difficult to move out of the informal sector for permanent higher-paying jobs in other sectors, due to issues like lack of training (Naidoo, Packard, & Auwalin, 2015). Even if workers move to the formal sector, they will only earn the lowest-paying wages, an option most workers would not prefer even if it comes with insurance benefits, highlighting why this sectoral shift becomes more rigid throughout the years.…”
Section: Shift In Job Sectors and Increased Mobility From Import-oriementioning
confidence: 99%
“…On one hand, such policies may incentivize employers to provide productive opportunities to youth; on the other, improperly designed or implemented policies might have detrimental effects on youths' prospects in the labor market-and not only in the short term. Ample research has found that exposure to higher levels of unemployment and poor quality/informal employment during one's youth has scarring effects on labor market outcomes later in life, whether in the form of shorter employment spells and/or lower wages (Cruces et al 2012 for Argentina/Brazil;Naidoo et al 2015 for Indonesia; Yu 2012 for Japan).…”
Section: Box 62mentioning
confidence: 99%
“…Recent evidence from Indonesia has correlated youth unemployment with increased entry into the informal sector (Naidoo et al 2014). Youth who resort to informal employment early on see very little mobility in their careers and find it especially difficult to transition to formal sector work .…”
Section: Box 23 Youth Inactivity and Informal Employment In Indonesiamentioning
confidence: 99%